PENGARUH VOLUME PEMBERIAN AIR DAN KONSENTRASI PUPUK DAUN TERHADAP PERTUMBUHAN VEGETATIF TANAMAN ANGGREK Dendrobium undulatum - Eka Riana Sari; Cicik Udayana; Tatik Wardiyati (BUANA SAINS, 2011)
Orchid are one kinds of highest estetic flower in the international orchid market. The aim of the research is evaluate application of fertilizer and watering Dendrobium undulatum at vegetative phase. This research was conducted at Venus Orchids during April – July 2010 location in Tegalweru village, Dau, Malang. Factorial Randomized Completed Design with three replication. The treatment are: Factor I: Concentration of fertilizer, P1: 1,0 g/l, P2: 1,5 g/l, P3: 2,0 g/l, P4: 2,5 g/l, P5: 3,0 g/l. Factor II: Watering volume, V1: 10 cc/pot, V2: 15 cc/pot, V3: 20 cc/pot. The result showed there is interaction between the usage of leaf fertilizer concentration and water volume on vegetative growth Dendrobium undulatum. There is no significant difference on parameters number of leaf, height of plant, number of root and fresh weight of plant with leaf fertilizer concentration on Dendrobium undulatum at vegetative phase. There significant difference on parameters leaf area, height of plant, and fresh weight of plant with usage water volume on Dendrobium undulatum, on water volume 10 cc/pot showed result better than usage water volume 15 cc/pot, or 20 cc/pot